A two-dimensional maci@zif-8 host-guest passivation body composite material and preparation and application thereof

CN117866217BActive Publication Date: 2026-10-30SHANGHAI UNIV OF ENG SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310478384.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2026-10-30
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

然而三维MOFs材料的大尺寸和绝缘特性限制了MOFs材料在钙钛矿太阳能电池中的应用

Benefits of technology

[0028](1)本发明采用混合溶剂法制备了形貌、尺寸均匀,易于成膜的二维ZIF-8材料,制备工艺简单,材料结晶性好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117866217B_ABST
    Figure CN117866217B_ABST
Patent Text Reader

Abstract

The application relates to a two-dimensional MACl@ZIF-8 host-guest passivation body composite material and a preparation and application thereof, and the composite material is prepared by the following steps: (1) dissolving a zinc salt in a mixed solvent of N, N-dimethylformamide and ethanol, stirring to obtain solution A; then dissolving 2-methyl imidazole in a mixed solvent of N, N-dimethylformamide and ethanol, stirring to obtain solution B; (2) pouring solution A into solution B, carrying out mixing reaction, continuing aging of the obtained reaction product solution, carrying out centrifugal separation and washing, and obtaining ZIF-8 nanosheets; (3) stirring the obtained ZIF-8 nanosheets in a DMF supersaturated solution of methylammonium chloride, carrying out centrifugal separation and cleaning of the obtained reaction product, and obtaining the MACl@ZIF-8 composite material, namely the target product. The material has the advantages of simple preparation process, good chemical stability, smooth and dense film, and the like, and when the material is applied to a buried bottom interface between an electron transport layer and a perovskite active layer, the photovoltaic performance of a perovskite solar cell can be greatly improved, and the stability of the device can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of perovskite solar cell technology, and relates to a two-dimensional MACl@ZIF-8 host-guest passivation composite material and its preparation and application. Background Technology

[0002] Solar cells are clean and pollution-free, providing a continuous supply of electricity and are convenient to use. Currently, commercially available solar cells are mainly crystalline silicon cells, but their cost is high. Therefore, developing new, low-cost solar cells is essential. After more than a decade of development, perovskite solar cells have achieved performance almost comparable to the most mature crystalline silicon solar cells, thus possessing great application potential. The structure of a perovskite solar cell generally consists of conductive glass, an electron transport layer (ETL), a hole transport layer (HTL), a perovskite absorber layer, and metal electrodes. As a crucial component of perovskite solar cells, the hole transport layer plays a vital role in optimizing power conversion efficiency and long-term device stability; however, the efficiency and stability of its fabrication remain bottlenecks restricting the further development and application of perovskite solar cells.

[0003] Metal-organic frameworks (MOFs), as a class of inorganic-organic crystalline hybrid materials, possess a wide range of unique properties. Their multimodal porosity and open architecture enable efficient large-scale transport. The application of MOFs in perovskite solar cells remains to be explored. Current research mainly focuses on three-dimensional MOFs, utilizing their scaffold structure and ligand groups to improve device performance. However, the large size and insulating properties of three-dimensional MOFs limit their application in perovskite solar cells. Summary of the Invention

[0004] The purpose of this invention is to provide a two-dimensional MACl@ZIF-8 host-guest passivation composite material, its preparation and application, so as to utilize the host-guest structure of MACl@ZIF-8 to efficiently passivate defects at the buried interface and cation vacancies in the perovskite phase, thereby achieving simultaneous passivation of the buried interface and the perovskite phase, which significantly improves the photovoltaic performance and stability of the device.

[0005] The objective of this invention can be achieved through the following technical solutions:

[0006] One of the technical solutions of the present invention provides a method for preparing a two-dimensional MACl@ZIF-8 host-guest passivation composite material, comprising the following steps:

[0007] (1) Dissolve zinc salt in a mixed solvent of N,N-dimethylformamide and ethanol and stir to obtain solution A; then dissolve 2-methylimidazole in a mixed solvent of N,N-dimethylformamide and ethanol and stir to obtain solution B;

[0008] (2) Pour solution A into solution B, mix and react. After the resulting reaction product solution is further aged, centrifuge and wash to obtain ZIF-8 nanosheets.

[0009] (3) The obtained ZIF-8 nanosheets were stirred and reacted in a DMF supersaturated solution of methylammonium chloride. The reaction product was centrifuged and washed to obtain the MACl@ZIF-8 composite material, which is the target product.

[0010] Furthermore, in step (1), the zinc salt is one or more of zinc nitrate hexahydrate, zinc chloride, zinc acetate, and zinc sulfate.

[0011] Furthermore, in the mixed solvent of step (1), the volume ratio of N,N-dimethylformamide to ethanol is 1 to 2:1, preferably 1:1.

[0012] Furthermore, in step (1), the molar concentration of zinc salt in solution A is 0.02 to 0.05 M, preferably 0.03 M; and the molar concentration of 2-methylimidazole in solution B is 0.06 to 0.14 M, preferably 0.12 M.

[0013] Furthermore, in step (2), the amounts of solution A and solution B added satisfy the following: the molar ratio of zinc salt to 2-methylimidazole is 1:3-5, preferably 1:4.

[0014] Furthermore, in step (2), the temperature of the mixed reaction is 20-40℃ and the time is 20-30min.

[0015] Furthermore, in step (2), the aging time is 24 hours.

[0016] Furthermore, in step (3), the stirring reaction is carried out at room temperature (20-40°C) at a speed of 700 rpm for 24 hours.

[0017] The second technical solution of the present invention provides a two-dimensional MACl@ZIF-8 host-guest passivation composite material, which is prepared by any of the preparation methods described above.

[0018] The third technical solution of the present invention provides the application of a two-dimensional MACl@ZIF-8 host-guest passivation composite material, characterized in that the host-guest passivation composite material is used to passivate the buried interface of the electron transport layer / perovskite layer in perovskite solar cells.

[0019] Furthermore, the application process is as follows:

[0020] (A) First, the MACl@ZIF-8 composite material was dispersed in DMF to obtain a MACl@ZIF-8 dispersion;

[0021] (B) The SnO2 precursor solution is coated on the surface of the conductive substrate, and the electron transport layer is obtained by annealing once. The obtained MACl@ZIF-8 dispersion is then coated on the surface of the electron transport layer, and the mixture is annealed a second time. Next, the perovskite precursor solution is coated, and the mixture is annealed a third time to obtain the perovskite active layer. Then, the hole transport layer is coated, and finally the gold electrode is evaporated to obtain the complete battery device.

[0022] More preferably, the concentration of the MACl@ZIF-8 dispersion is 50–150 mg / mL, and more preferably 100 mg / mL.

[0023] More preferably, the conductive substrate is FTO or ITO.

[0024] More preferably, the coating method can be spin coating, spray coating or scraping coating, etc.

[0025] More preferably, the secondary annealing temperature after coating with MACl@ZIF-8 dispersion is 80-120°C and held for 10-30 min, preferably annealing at 100°C for 20 min.

[0026] This invention utilizes the porosity and open architecture of a two-dimensional metal-organic framework to prepare a host-guest modified material. This material exhibits good crystallinity and uniform size, and when dispersed in DMF, it is further introduced into the buried interface of perovskite solar cells. Experimental results show that the host-guest passivation system has a dual passivation effect on both the perovskite buried interface and the perovskite bulk phase, resulting in improved photoelectric conversion efficiency and excellent long-term stability of the device.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] (1) The present invention uses a mixed solvent method to prepare a two-dimensional ZIF-8 material with uniform morphology and size and easy film formation. The preparation process is simple and the material has good crystallinity.

[0029] (2) This invention utilizes the structural pore characteristics of ZIF-8 to pre-embed volatile ammonium salts (represented by MACl) to prepare a two-dimensional host-guest passivation system MACl@ZIF-8 for the first time, which is easy to be uniformly and densely distributed at the buried interface of perovskite.

[0030] (3) The MACl@ZIF-8 prepared by this invention can simultaneously and efficiently passivate the buried interface defects and perovskite bulk phase cation vacancies of perovskite solar cells, with high electron transport rate and good chemical stability.

[0031] (4) The MACl@ZIF-8 prepared by this invention has the effect of absorbing ultraviolet light, which can prevent the device from perovskite decomposition caused by ultraviolet light. Attached Figure Description

[0032] Figure 1 Scanning electron microscope image of MACl@ZIF-8 prepared in Example 1;

[0033] Figure 2 The XRD pattern of MACl@ZIF-8 prepared in Example 1;

[0034] Figure 3 Electron microscopy images of the perovskite thin films prepared in Example 1 before and after MACl@ZIF-8 modification;

[0035] Figure 4 Current-voltage curves of the perovskite solar cell based on SnO2 and MACl@ZIF-8 / SnO2 prepared in Example 1. Detailed Implementation

[0036] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.

[0037] In the following embodiments, unless otherwise specified, the raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0038] Example 1:

[0039] (1) Take 4 mmol of zinc nitrate hexahydrate and dissolve it in a mixed solvent of 120 mL of DMF and an equal volume of ethanol. Stir the mixed solution thoroughly to obtain solution A. Then dissolve 16 mmol of 2-MIM in the same mixed solvent and stir for 15 min to obtain solution B. Then quickly pour solution A into solution B and stir magnetically for 30 min to allow the two solutions to mix and react thoroughly.

[0040] (2) After aging the mixed solution obtained in step (1) for 24 hours, ZIF-8 nanosheets were collected by centrifugation. The product was then washed twice with ethanol and once with DMF.

[0041] (3) The ZIF-8 nanosheets obtained in step (2) were continuously stirred in a saturated solution of MACl in DMF to obtain MACl@ZIF-8 nanosheets. The product was collected by centrifugation and washed with ethanol. For further use, the wet precipitate was redispersed in DMF at a concentration of 100 mg / mL.

[0042] (4) Coat the SnO2 precursor solution (1 mol / L SnCl2·2H2O isopropanol solution) onto the FTO surface, anneal to obtain the electron transport layer, and then spin-coat the MACl@ZIF-8 solution from (3) onto the electron transport layer and anneal at 100℃ for 20 min. Subsequently, a perovskite precursor solution (a 1.4 mol / L perovskite precursor solution prepared by dissolving 18.2 mg cesium iodide (CsI), 26.7 mg methylammonium bromide (MABr), 199.8 mg formamidinium iodide (FAI), 573.9 mg lead iodide (PbI2), and 87.4 mg lead bromide (PbBr2) in 1 mL of a mixed solvent of DMF and DMSO (DMF:DMSO = 4:1)) was spin-coated onto this substrate. The solution was annealed at 105 °C to obtain the perovskite active layer, followed by spin-coating of a hole transport layer (Spiro-OMeTAD solution was prepared according to the following formulation for the hole transport layer: 13.125 μL of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) and 21.6 μL of...) 4-tert-butylpyridine (TBP) and 30 mg of Spiro-OMeTAD were dissolved in 825 μL of chlorobenzene. Finally, a gold electrode was deposited by vapor deposition to obtain the complete device (where the SnO2 electron transport layer is about 40 nm thick, the MACl@ZIF-8 layer is about 10 nm thick, the perovskite layer is about 700 nm thick, the Spiro-OMeTAD hole transport layer is about 200 nm thick, and the gold electrode is about 90 nm thick).

[0043] Figure 1 The image shows a scanning electron microscope (SEM) image of the MACl@ZIF-8 nanosheets prepared in Example 1. The image shows that the size of the MACl@ZIF-8 nanosheets is between 30 and 60 nm.

[0044] Figure 2 The image shows the XRD pattern of MACl@ZIF-8 prepared in Example 1. As can be seen from the image, ZIF-8 has good crystallinity before and after the MACl is embedded.

[0045] Figure 3 The images show scanning electron microscope (SEM) images of the perovskite thin films prepared in Example 1 before and after modification with MACl@ZIF-8 (left image is before modification, right image is after modification). As can be seen from the images, the grain size of the thin film increases significantly after the addition of the additive.

[0046] Figure 4 The current-voltage curve of the perovskite solar cell based on MACl@ZIF-8 modification prepared in Example 1 shows a short-circuit current density of 24.07 mA cm⁻¹. -2 The fill factor is 79.10%, the open-circuit voltage of the battery is 1.17V, and the photoelectric conversion efficiency is 22.10%.

[0047] Example 2:

[0048] (1) Dissolve 3 mmol of zinc nitrate hexahydrate in a mixed solvent of 120 mL of DMF and an equal volume of ethanol, and stir the mixed solution thoroughly to obtain solution A; then dissolve 12 mmol of 2-MIM in the same mixed solvent as above, stir for 15 min to obtain solution B, and then quickly pour solution A into solution B, and stir magnetically for 30 min to make the two solutions fully mix and react.

[0049] (2) After aging the mixed solution obtained in step (1) for 24 hours, ZIF-8 nanosheets were collected by centrifugation. The product was then washed twice with ethanol and once with DMF.

[0050] (3) The ZIF-8 nanosheets obtained in step (2) were continuously stirred in a saturated solution of MACl in DMF to obtain MACl@ZIF-8 nanosheets. The product was collected by centrifugation and washed with ethanol. For further use, the wet precipitate was redispersed in DMF at a concentration of 100 mg / mL.

[0051] (4) The SnO2 precursor solution (1 mol / L SnCl2·2H2O isopropanol solution) was coated onto the FTO surface and annealed to obtain an electron transport layer. Then, the MACl@ZIF-8 solution from (3) was spin-coated onto the electron transport layer and annealed at 100°C for 20 min. Subsequently, a perovskite precursor solution (18.2 mg CsI, 26.7 mg MABr, 199.8 mg FAI, 573.9 mg PbI2, and 87.4 mg PbBr2 dissolved in 1 mL of a mixed solvent of DMF and DMSO (DMF:DMSO = 4:1) was spin-coated onto this substrate and annealed at 105°C to obtain a perovskite active layer. Then, a hole transport layer was spin-coated (Spiro-OMeTAD solution was prepared according to the following formula: for the hole transport layer: 13.125 μL Li-TFSI and 21.6 μL... TBP and 30 mg of Spiro-OMeTAD were dissolved in 825 μL of chlorobenzene. Finally, a gold electrode was deposited to obtain the complete device (where the SnO2 electron transport layer thickness was 30–50 nm, the MACl@ZIF-8 layer thickness was approximately 5–15 nm, the perovskite layer thickness was approximately 600–800 nm, the Spiro-OMeTAD hole transport layer thickness was approximately 150–250 nm, and the gold electrode thickness was approximately 90 nm).

[0052] Example 3:

[0053] (1) Take 4 mmol of zinc nitrate hexahydrate and dissolve it in a mixed solvent of 120 mL of DMF and an equal volume of ethanol. Stir the mixed solution thoroughly to obtain solution A. Then dissolve 12 mmol of 2-MIM in the same mixed solvent and stir for 15 min to obtain solution B. Then quickly pour solution A into solution B and stir magnetically for 30 min to allow the two solutions to mix and react thoroughly.

[0054] (2) After aging the mixed solution obtained in step (1) for 24 hours, ZIF-8 nanosheets were collected by centrifugation. The product was then washed twice with ethanol and once with DMF.

[0055] (3) The ZIF-8 nanosheets obtained in step (2) were continuously stirred in a saturated solution of MACl in DMF to obtain MACl@ZIF-8 nanosheets. The product was collected by centrifugation and washed with ethanol. For further use, the wet precipitate was redispersed in DMF at a concentration of 100 mg / mL.

[0056] (4) The SnO2 precursor solution was coated onto the FTO surface and annealed to obtain the electron transport layer. The MACl@ZIF-8 solution from (3) was then spin-coated onto the electron transport layer and annealed at 100°C for 20 min. Subsequently, the perovskite precursor solution was spin-coated onto this substrate and annealed at 105°C to obtain the perovskite active layer. Then, the hole transport layer was spin-coated, and finally, the gold electrode was deposited by vapor deposition to obtain the complete device.

[0057] Example 4:

[0058] (1) Take 4 mmol of zinc chloride hexahydrate and dissolve it in a mixed solvent of 120 mL of DMF and an equal volume of ethanol. Stir the mixed solution thoroughly to obtain solution A. Then dissolve 16 mmol of 2-MIM in the same mixed solvent and stir for 15 min to obtain solution B. Then quickly pour solution A into solution B and stir magnetically for 30 min to allow the two solutions to mix and react thoroughly.

[0059] (2) After aging the mixed solution obtained in step (1) for 24 hours, ZIF-8 nanosheets were collected by centrifugation. The product was then washed twice with ethanol and once with DMF.

[0060] (3) The ZIF-8 nanosheets obtained in step (2) were continuously stirred in a saturated solution of MACl in DMF to obtain MACl@ZIF-8 nanosheets. The product was collected by centrifugation and washed with ethanol. For further use, the wet precipitate was redispersed in DMF at a concentration of 100 mg / mL.

[0061] (4) The SnO2 precursor solution (1 mol / L SnCl2·2H2O isopropanol solution) was coated onto the FTO surface and annealed to obtain an electron transport layer. Then, the MACl@ZIF-8 solution from (3) was spin-coated onto the electron transport layer and annealed at 100°C for 20 min. Subsequently, a perovskite precursor solution (18.2 mg CsI, 26.7 mg MABr, 199.8 mg FAI, 573.9 mg PbI2, and 87.4 mg PbBr2 dissolved in 1 mL of a mixed solvent of DMF and DMSO (DMF:DMSO = 4:1) was spin-coated onto this substrate and annealed at 105°C to obtain a perovskite active layer. Then, a hole transport layer was spin-coated (Spiro-OMeTAD solution was prepared according to the following formula: for the hole transport layer: 13.125 μL Li-TFSI and 21.6 μL... TBP and 30 mg of Spiro-OMeTAD were dissolved in 825 μL of chlorobenzene. Finally, a gold electrode was deposited to obtain the complete device (where the SnO2 electron transport layer thickness is 30-50 nm, the MACl@ZIF-8 layer thickness is approximately 5-15 nm, the perovskite layer thickness is approximately 600-800 nm, the Spiro-OMeTAD hole transport layer thickness is approximately 150-250 nm, and the gold electrode thickness is approximately 90 nm).

[0062] Example 5:

[0063] (1) Take 4 mmol of zinc acetate dihydrate and dissolve it in a mixed solvent of 120 mL of DMF and an equal volume of ethanol. Stir the mixed solution thoroughly to obtain solution A. Then dissolve 12 mmol of 2-MIM in the same mixed solvent and stir for 15 min to obtain solution B. Then quickly pour solution A into solution B and stir magnetically for 30 min to allow the two solutions to mix and react thoroughly.

[0064] (2) After aging the mixed solution obtained in step (1) for 24 hours, ZIF-8 nanosheets were collected by centrifugation. The product was then washed twice with ethanol and once with DMF.

[0065] (3) The ZIF-8 nanosheets obtained in step (2) were continuously stirred in a saturated solution of MACl in DMF to obtain MACl@ZIF-8 nanosheets. The product was collected by centrifugation and washed with ethanol. For further use, the wet precipitate was redispersed in DMF at a concentration of 100 mg / mL.

[0066] (4) The SnO2 precursor solution (1 mol / L SnCl2·2H2O isopropanol solution) was coated onto the FTO surface and annealed to obtain an electron transport layer. Then, the MACl@ZIF-8 solution from (3) was spin-coated onto the electron transport layer and annealed at 100°C for 20 min. Subsequently, a perovskite precursor solution (18.2 mg CsI, 26.7 mg MABr, 199.8 mg FAI, 573.9 mg PbI2, and 87.4 mg PbBr2 dissolved in 1 mL of a mixed solvent of DMF and DMSO (DMF:DMSO = 4:1) was spin-coated onto this substrate and annealed at 105°C to obtain a perovskite active layer. Then, a hole transport layer was spin-coated (Spiro-OMeTAD solution was prepared according to the following formula: for the hole transport layer: 13.125 μL Li-TFSI and 21.6 μL... TBP and 30 mg of Spiro-OMeTAD were dissolved in 825 μL of chlorobenzene. Finally, a gold electrode was deposited to obtain the complete device (where the SnO2 electron transport layer thickness is 30-50 nm, the MACl@ZIF-8 layer thickness is approximately 5-15 nm, the perovskite layer thickness is approximately 600-800 nm, the Spiro-OMeTAD hole transport layer thickness is approximately 150-250 nm, and the gold electrode thickness is approximately 90 nm).

[0067] Example 6:

[0068] (1) Take 4 mmol of zinc nitrate hexahydrate and dissolve it in a mixed solvent of 120 mL of DMF and an equal volume of ethanol. Stir the mixed solution thoroughly to obtain solution A. Then dissolve 12 mmol of 2-MIM in the same mixed solvent and stir for 15 min to obtain solution B. Then quickly pour solution A into solution B and stir magnetically for 30 min to allow the two solutions to mix and react thoroughly.

[0069] (2) After aging the mixed solution obtained in step (1) for 24 hours, ZIF-8 nanosheets were collected by centrifugation. The product was then washed twice with ethanol and once with DMF.

[0070] (3) The ZIF-8 nanosheets obtained in step (2) were continuously stirred in a saturated solution of MACl in DMF to obtain MACl@ZIF-8 nanosheets. The product was collected by centrifugation and washed with ethanol. For further use, the wet precipitate was redispersed in DMF at a concentration of 150 mg / mL.

[0071] (4) The SnO2 precursor solution (1 mol / L SnCl2·2H2O isopropanol solution) was coated onto the FTO surface and annealed to obtain an electron transport layer. Then, the MACl@ZIF-8 solution from (3) was spin-coated onto the electron transport layer and annealed at 100°C for 20 min. Subsequently, a perovskite precursor solution (18.2 mg CsI, 26.7 mg MABr, 199.8 mg FAI, 573.9 mg PbI2, and 87.4 mg PbBr2 dissolved in 1 mL of a mixed solvent of DMF and DMSO (DMF:DMSO = 4:1) was spin-coated onto this substrate and annealed at 105°C to obtain a perovskite active layer. Then, a hole transport layer was spin-coated (Spiro-OMeTAD solution was prepared according to the following formula: for the hole transport layer: 13.125 μL Li-TFSI and 21.6 μL... TBP and 30 mg of Spiro-OMeTAD were dissolved in 825 μL of chlorobenzene. Finally, a gold electrode was deposited to obtain the complete device (where the SnO2 electron transport layer thickness is 30-50 nm, the MACl@ZIF-8 layer thickness is approximately 5-15 nm, the perovskite layer thickness is approximately 600-800 nm, the Spiro-OMeTAD hole transport layer thickness is approximately 150-250 nm, and the gold electrode thickness is approximately 90 nm).

[0072] Example 7:

[0073] (1) Take 4 mmol of zinc nitrate hexahydrate and dissolve it in a mixed solvent of 120 mL of DMF and an equal volume of ethanol. Stir the mixed solution thoroughly to obtain solution A. Then dissolve 12 mmol of 2-MIM in the same mixed solvent and stir for 15 min to obtain solution B. Then quickly pour solution A into solution B and stir magnetically for 30 min to allow the two solutions to mix and react thoroughly.

[0074] (2) After aging the mixed solution obtained in step (1) for 24 hours, ZIF-8 nanosheets were collected by centrifugation. The obtained product was then washed twice with ethanol and once with DMF.

[0075] (3) The ZIF-8 nanosheets obtained in step (2) were continuously stirred in a saturated solution of MACl in DMF to obtain MACl@ZIF-8 nanosheets. The product was collected by centrifugation and washed with ethanol. For further use, the wet precipitate was redispersed in DMF at a concentration of 100 mg / mL.

[0076] (4) The SnO2 precursor solution (1 mol / L SnCl2·2H2O isopropanol solution) was coated onto the FTO surface and annealed to obtain an electron transport layer. Then, the MACl@ZIF-8 solution from (3) was spin-coated onto the electron transport layer and annealed at 80°C for 20 min. Subsequently, a perovskite precursor solution (18.2 mg CsI, 26.7 mg MABr, 199.8 mg FAI, 573.9 mg PbI2, and 87.4 mg PbBr2 dissolved in 1 mL of a mixed solvent of DMF and DMSO (DMF:DMSO = 4:1) was spin-coated onto this substrate and annealed at 105°C to obtain a perovskite active layer. Then, a hole transport layer was spin-coated (Spiro-OMeTAD solution was prepared according to the following formula: for the hole transport layer: 13.125 μL Li-TFSI and 21.6 μL... TBP and 30 mg of Spiro-OMeTAD were dissolved in 825 μL of chlorobenzene. Finally, a gold electrode was deposited to obtain the complete device (where the SnO2 electron transport layer thickness is 30-50 nm, the MACl@ZIF-8 layer thickness is approximately 5-15 nm, the perovskite layer thickness is approximately 600-800 nm, the Spiro-OMeTAD hole transport layer thickness is approximately 150-250 nm, and the gold electrode thickness is approximately 90 nm).

[0077] Example 8:

[0078] (1) Take 4 mmol of zinc nitrate hexahydrate and dissolve it in a mixed solvent of 120 mL of DMF and an equal volume of ethanol. Stir the mixed solution thoroughly to obtain solution A. Then dissolve 12 mmol of 2-MIM in the same mixed solvent and stir for 15 min to obtain solution B. Then quickly pour solution A into solution B and stir magnetically for 30 min to allow the two solutions to mix and react thoroughly.

[0079] (2) After aging the mixed solution obtained in step (1) for 24 hours, ZIF-8 nanosheets were collected by centrifugation. The obtained product was then washed twice with ethanol and once with DMF.

[0080] (3) The ZIF-8 nanosheets obtained in step (2) were continuously stirred in a saturated solution of MACl in DMF to obtain MACl@ZIF-8 nanosheets. The product was collected by centrifugation and washed with ethanol. For further use, the wet precipitate was redispersed in DMF at a concentration of 100 mg / mL.

[0081] (4) The SnO2 precursor solution (1 mol / L SnCl2·2H2O isopropanol solution) was coated onto the FTO surface and annealed to obtain an electron transport layer. Then, the MACl@ZIF-8 solution from (3) was spin-coated onto the electron transport layer and annealed at 100°C for 10 min. Subsequently, a perovskite precursor solution (18.2 mg CsI, 26.7 mg MABr, 199.8 mg FAI, 573.9 mg PbI2, and 87.4 mg PbBr2 dissolved in 1 mL of a mixed solvent of DMF and DMSO (DMF:DMSO = 4:1) was spin-coated onto this substrate and annealed at 105°C to obtain a perovskite active layer. Then, a hole transport layer was spin-coated (Spiro-OMeTAD solution was prepared according to the following formula: for the hole transport layer: 13.125 μL Li-TFSI and 21.6 μL... TBP and 30 mg of Spiro-OMeTAD were dissolved in 825 μL of chlorobenzene. Finally, a gold electrode was deposited to obtain the complete device (where the SnO2 electron transport layer thickness is 30-50 nm, the MACl@ZIF-8 layer thickness is approximately 5-15 nm, the perovskite layer thickness is approximately 600-800 nm, the Spiro-OMeTAD hole transport layer thickness is approximately 150-250 nm, and the gold electrode thickness is approximately 90 nm).

[0082] Example 9:

[0083] (1) Take 4 mmol of zinc nitrate hexahydrate and dissolve it in a mixed solvent of 120 mL of DMF and an equal volume of ethanol. Stir the mixed solution thoroughly to obtain solution A. Then dissolve 12 mmol of 2-MIM in the same mixed solvent and stir for 15 min to obtain solution B. Then quickly pour solution A into solution B and stir magnetically for 30 min to allow the two solutions to mix and react thoroughly.

[0084] (2) After aging the mixed solution obtained in step (1) for 24 hours, ZIF-8 nanosheets were collected by centrifugation. The obtained product was then washed twice with ethanol and once with DMF.

[0085] (3) The ZIF-8 nanosheets obtained in step (2) were continuously stirred in a saturated solution of MACl in DMF to obtain MACl@ZIF-8 nanosheets. The product was collected by centrifugation and washed with ethanol. For further use, the wet precipitate was redispersed in DMF at a concentration of 100 mg / mL.

[0086] (4) The SnO2 precursor solution (1 mol / L SnCl2·2H2O isopropanol solution) was coated onto the ITO surface and annealed to obtain an electron transport layer. Then, the MACl@ZIF-8 solution from (3) was spin-coated onto the electron transport layer and annealed at 100°C for 20 min. Subsequently, a perovskite precursor solution (18.2 mg CsI, 26.7 mg MABr, 199.8 mg FAI, 573.9 mg PbI2, and 87.4 mg PbBr2 dissolved in 1 mL of a mixed solvent of DMF and DMSO (DMF:DMSO = 4:1) was spin-coated onto this substrate and annealed at 105°C to obtain a perovskite active layer. Then, a hole transport layer was spin-coated (Spiro-OMeTAD solution was prepared according to the following formula: for the hole transport layer: 13.125 μL Li-TFSI and 21.6 μL... TBP and 30 mg of Spiro-OMeTAD were dissolved in 825 μL of chlorobenzene. Finally, a gold electrode was deposited to obtain the complete device (where the SnO2 electron transport layer thickness was 30–50 nm, the MACl@ZIF-8 layer thickness was approximately 5–15 nm, the perovskite layer thickness was approximately 600–800 nm, the Spiro-OMeTAD hole transport layer thickness was approximately 150–250 nm, and the gold electrode thickness was approximately 90 nm).

[0087] Example 10:

[0088] (1) Take 4 mmol of zinc nitrate hexahydrate and dissolve it in a mixed solvent of 120 mL of DMF and an equal volume of ethanol. Stir the mixed solution thoroughly to obtain solution A. Then dissolve 12 mmol of 2-MIM in the same mixed solvent and stir for 15 min to obtain solution B. Then quickly pour solution A into solution B and stir magnetically for 30 min to allow the two solutions to mix and react thoroughly.

[0089] (2) After aging the mixed solution obtained in step (1) for 24 hours, ZIF-8 nanosheets were collected by centrifugation. The product was then washed twice with ethanol and once with DMF.

[0090] (3) The ZIF-8 nanosheets obtained in step (2) were continuously stirred in a saturated solution of MACl in DMF to obtain MACl@ZIF-8 nanosheets. The product was collected by centrifugation and washed with ethanol. For further use, the wet precipitate was redispersed in DMF at a concentration of 100 mg / mL.

[0091] (4) The SnO2 precursor solution (1 mol / L SnCl2·2H2O isopropanol solution) was coated onto the FTO surface and annealed to obtain an electron transport layer. Then, the MACl@ZIF-8 solution from (3) was sprayed onto the electron transport layer and annealed at 100°C for 20 min. Subsequently, a perovskite precursor solution (18.2 mg CsI, 26.7 mg MABr, 199.8 mg FAI, 573.9 mg PbI2, and 87.4 mg PbBr2 dissolved in 1 mL of a mixed solvent of DMF and DMSO (DMF:DMSO = 4:1) was spin-coated onto this substrate and annealed at 105°C to obtain a perovskite active layer. Then, a hole transport layer was spin-coated (Spiro-OMeTAD solution was prepared according to the following formula: for the hole transport layer: 13.125 μL Li-TFSI and 21.6 μL... TBP and 30 mg of Spiro-OMeTAD were dissolved in 825 μL of chlorobenzene. Finally, a gold electrode was deposited to obtain the complete device (where the SnO2 electron transport layer thickness is 30-50 nm, the MACl@ZIF-8 layer thickness is approximately 5-15 nm, the perovskite layer thickness is approximately 600-800 nm, the Spiro-OMeTAD hole transport layer thickness is approximately 150-250 nm, and the gold electrode thickness is approximately 90 nm).

[0092] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a two-dimensional MACl@ZIF-8 host-guest passivation composite material, characterized in that, Includes the following steps: (1) Dissolve zinc salt in a mixed solvent of N,N-dimethylformamide and ethanol and stir to obtain solution A; then dissolve 2-methylimidazole in a mixed solvent of N,N-dimethylformamide and ethanol and stir to obtain solution B; (2) Pour solution A into solution B, mix and react. After the resulting reaction product solution is further aged, centrifuge and wash to obtain ZIF-8 nanosheets. (3) The obtained ZIF-8 nanosheets were stirred and reacted in a DMF supersaturated solution of methylammonium chloride. The reaction product was centrifuged and washed to obtain the MACl@ZIF-8 composite material, which is the target product.

2. The method for preparing a two-dimensional MACl@ZIF-8 host-guest passivation composite material according to claim 1, characterized in that, In step (1), the zinc salt is one or more of zinc nitrate hexahydrate, zinc chloride, zinc acetate, and zinc sulfate.

3. The method for preparing a two-dimensional MACl@ZIF-8 host-guest passivation composite material according to claim 1, characterized in that, In the mixed solvent of step (1), the volume ratio of N,N-dimethylformamide to ethanol is 1 to 2:

1.

4. The method for preparing a two-dimensional MACl@ZIF-8 host-guest passivation composite material according to claim 1, characterized in that, In step (1), the molar concentration of zinc salt in solution A is 0.02–0.05 M; the molar concentration of 2-methylimidazole in solution B is 0.06–0.14 M.

5. The method for preparing a two-dimensional MACl@ZIF-8 host-guest passivation composite material according to claim 1, characterized in that, In step (2), the amount of solution A and solution B added satisfies the following condition: the molar ratio of zinc salt to 2-methylimidazole is 1:3-5.

6. The method for preparing a two-dimensional MACl@ZIF-8 host-guest passivation composite material according to claim 1, characterized in that, In step (2), the temperature of the mixing reaction is 20-40℃ and the time is 20-30 min; The aging time is 24 hours.

7. The method for preparing a two-dimensional MACl@ZIF-8 host-guest passivation composite material according to claim 1, characterized in that, In step (3), the stirring reaction is carried out at room temperature (20-40°C) at a speed of 700 rpm for 24 hours.

8. A two-dimensional MACl@ZIF-8 host-guest passivation composite material, which is prepared by the preparation method according to any one of claims 1-7.

9. The application of the two-dimensional MACl@ZIF-8 host-guest passivation composite material as described in claim 8, characterized in that, This host-guest passivator composite material is used to passivate the buried interface of the electron transport layer / perovskite layer in perovskite solar cells.

10. The application of the two-dimensional MACl@ZIF-8 host-guest passivation composite material according to claim 9, characterized in that, The application process is as follows: (A) First, the MACl@ZIF-8 composite material was dispersed in DMF to obtain a MACl@ZIF-8 dispersion; (B) The SnO2 precursor solution is coated on the surface of the conductive substrate, and the electron transport layer is obtained by annealing once. The obtained MACl@ZIF-8 dispersion is then coated on the surface of the electron transport layer, and the mixture is annealed a second time. Next, the perovskite precursor solution is coated, and the mixture is annealed a third time to obtain the perovskite active layer. Then, the hole transport layer is coated, and finally the gold electrode is evaporated to obtain the complete battery device.

Citation Information

Patent Citations

  • Reparation method of gradient porous metal organic framework ZIF (Zeolitic Imidazolate Framework)-8

    CN108129670A

  • Preparation method and application of activated compatibilizer for repairing failed lead-acid storage battery

    CN112054253A